Excellent color quality of phosphor converted white light emitting diodes with remote phosphor geometry - Thinh Cong Tran; Nguyen Doan Quoc Anh; Nguyen Thi Phuong Loan (Universitas Ahmad Dahlan, 2020)
The remote phosphor structure is disadvantageous in color quality but more convenient in luminous flux when compared to conformal phosphor or in-cup phosphor structure. From this disadvantage, there are many studies to improve the color quality of the remote phosphor structure. This research will propose a dual-layer remote phosphor structure to improve color rendering index (CRI) and color quality scale (CQS) of WLEDs. The WLED package with color temperature of 8500 K is utilized in this study. The idea of the study is to locate a layer of phosphor green Y2O2S:Tb3+ or red ZnS:Sn2+ on the yellow phosphor YAG:Ce3+ film, and then finding the suitable added concentration of ZnS:Sn2+ to match the highest color quality. The results showed that ZnS:Sn2+ brings great benefits to increase CRI and CQS. The greater the ZnS:Sn2+ concentration is, the higher the CRI and CQS become owing to the rise in red light components in WLEDs. Meanwhile, the green Y2O2S:Tb3+ phosphor brings benefits to luminous flux. However, the decrease in luminous flux and color quality occurs when the concentration of ZnS:Sn2+ and Y2O2S:Tb3+ exceeds the corresponding level. This is proved by applying Mie-scattering theory and Lambert-Beer's law. The results of articles are important for WLEDs’ fabrication having higher white light quality.